EVALUATION OF CROSS PROTECTION AGAINST AVIAN INFLUENZA VIRUS (AIV) AND NEWCASTLE DISEASE VIRUS (NDV) IN BROILER CHICKENS AFTER VACCINATION IN PAKISTAN - M. Ali; B. Muneer; T. Yaqub; S. F. Rehmani; M. Naeem (Journal of Animal and Plant Sciences, 2016)
Newcastle Disease is still endemic in Pakistan’s poultry industry and responsible for great economic losses and high mortalities. Avian Influenza Virus has been involved in production losses in past few years, with or without the association of Newcastle Disease in the field. Therefore, present study was planned to evaluate the cross protection between Avian Influenza Virus and Newcastle Disease Virus. Local field isolates for both viruses were collected from recent outbreaks and used for inactivated vaccine formation. Results revealed that geometric mean titer values assessed up to 6 (log2) or above, provided excellent protection to chickens when challenged with viscerotropic velogenic form of Newcastle Disease Virus (vvNDV). Groups vaccinated with inactivated Newcastle Disease vaccine and bivalent vaccine (containing Newcastle Disease Virus and Avian Influenza Virus) provided 90 to 100% protection following challenge with vvNDV. Oil emulsified vaccine provided excellent protection using local field isolate against Newcastle Disease. Moreover, inactivated Avian Influenza vaccine produced 60% cross protection using local field isolate when challenged with vvNDV. Regression analysis showed significant (P< 0.01) correlation between titers against Avian Influenza versus Newcastle Disease, though the group was only vaccinated with Avian Influenza vaccine. Moreover, the group vaccinated with Newcastle Disease vaccine produced titers against Newcastle Disease as well as Avian Influenza despite the group was not vaccinated against Avian Influenza Virus and correlation among them was found highly significant (P< 0.001).
Keywords: Newcastle disease; Avian influenza virus; Cross protection; Inactivated vaccine